Development of a Software Usage Loyalty Model by Analysing the Causal Relationships between Software Quality, Customer Satisfaction, Trust, and Experience in the Access by KAI Application - Mutiaraputi, Angela Regine; Pujiyanto, Eko; Priyandari, Yusuf (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2000)
Trains are a popular mode of long-distance transportation in Indonesia due to their advantages in travel time, comfort, and safety. In 2023, train passengers increased by 40.6% to 270 million people, with most tickets booked through mobile applications. PT Kereta Api Indonesia (KAI) offers online ticket booking services through the Access by KAI application, which, despite its increased usage, has received many negative reviews regarding its performance on the Google Play Store. This research aims to develop a model of software usage loyalty using nine software quality variables from ISO/IEC 25010:2023 product quality and the PLS-SEM (Partial Least Squares-Structural Equation Modelling) method to analyse the causal relationships between software quality, customer satisfaction, trust, experience, and loyalty. The results show that functional suitability and safety have a significant positive indirect effect on customer loyalty through customer satisfaction. Additionally, functional suitability, safety, customer trust, and customer experience have a significant positive direct effect on customer satisfaction, while customer trust and customer satisfaction have a significant positive direct effect on customer loyalty. Based on these findings, priority suggestions were developed to improve the Access by KAI application.